PRELIMINARY PHYTOCHEMICAL SCREENING AND IN VITRO ANTI-MICROBIAL ACTIVITY OF ETHANOLIC EXTRACT OF DELONIX REGIA (HOOK) RAF. BARK (FAMILY-LEGUMINOSAE) - Gupta, Bikash; Dash, Biswajit; Paul, Sujata; Bora, Aditya (International Journal of Current Pharmaceutical Research, 2018)
Objective: To estimate the anti-microbial activity of ethanolic extract of Delonix regia (Hook.) Raf (family-Leguminosae) in association with phytochemical analysis. Methods: The ethanolic extract of the bark of Delonix regia (Hook.) Raf was prepared and investigate for phytochemical constituents using standard methods. Antimicrobial activity of ethanolic extract of were carried out against one Gram positive bacteria= Staphylococcus aureus and one Gram negative bacteria= Escherichia coli. The anti-fungal activity of the plant extract was evaluated on Candida albicans. The testing was done by the disc diffusion method. A zone of inhibition of ethanolic extract was compared with that of standard Amikacin for anti-bacterial activities and Fluconazole for anti-fungal activity. Results: The present investigation shows the phytochemical analysis, antimicrobial activity of the ethanolic extract of the bark of Delonix regia (Hook.) Raf. Various phytochemical analyses revealed the presence of alkaloids, anthraquinone, phenol, terpenes, cardenolides, phlobatannins, tannin, chalcones, steroids. The anti-microbial activity of the ethanolic extract of the plant showed significant results against all three of the test organisms. Conclusion: The present study concluded that ethanolic extract of the bark of Delonix regia (Hook.) Raf contains the high existence of phytochemicals. The ethanolic extract of the plant was found to possess promising antimicrobial activity when compared with the standards.